Association Between Trajectory Patterns of Body Mass Index Change Up to 10 Months and Early Gut Microbiota in Preterm Infants - Qiu, Jun; Zhou, Changci; Xiang, Shiting; Dong, Jie; Zhu, Qifeng; Yin, Jieyun; Lu, Xiulan; Xiao, Zhenghui (Frontiers in Microbiology, 2022)
Overweight and obesity are growing problems worldwide. Recent research suggests that the gut microbiota plays an important role in the occurrence and development of overweight and obesity, and the early life gut microbiota may be correlated with weight gain and later growth. Therefore, the early gut microbiota may be a crucial factor in promoting healthy growth and development of newborns with potential influences for later life. However, the association between neonatal gut microbiota, particularly in preterm infants, and overweight and obesity remains unclear. To evaluate the relationship between gut microbiota and body mass index (BMI) growth trajectories in preterm infants, we determined microbial composition in fecal samples within 3 months after birth from 75 preterm infants hospitalized in neonatal intensive care unit (NICU) of Hunan Children's Hospital from August 1st 2018 and October 31st 2019, and collected their physical growth information during 0-10 months. Latent growth mixture models were used to estimate growth trajectories of infantile BMI. We performed 16S rDNA gene sequencing on the gut microbiota samples by Illumina Miseq platform and then analyzed the relationship between the gut microbiota and the BMI growth trajectories. Our results demonstrated that there were 63, 305 and 61 OTUs in higher BMI group (n=18), lower BMI group (n=51) and BMI catch-up group (n=6), respectively. There were significant differences in the abundance of the gut microbiota but no significant differences in the diversity of it between the lower BMI group and the higher BMI group. The BMI growth trajectories could not be clearly distinguished because principal component analysis showing that gut microbiota composition among three groups were similar. The three groups were dominated by Firmicutes and Proteobacteria in gut microbiota composition, and the abundance of Lactobacillus in the higher BMI group was significantly different from the lower BMI group. Overall, these findings will provide etiological references, prevention and treatments for childhood obesity.